Planning for Full Employment - Ministry of Commerce & Industry Government of India (Ministry of Commerce & Industry Government of India, 1954)
The idea of constituting a Board of this kind came up for consideration as early as in 1951, when the Planning Commission began grappling with the problems of agriculture and rural economic development. A question of utmost importance was the availability of the requisite capital resources for industrial planning and of finding gainful occupation for the teeming millions which lived under submarginal conditions. It was recognised that capital was scarce in India whereas manpower was abundant. Rapid capital formation was impossible in a backward and under-developed economy, unless the vast manpower was productively employed. Development of village industries inevitably came to the forefront. How best this task could be achieved was discussed in its various aspects.
Ministry of Commerce & Industry Government of India
Ministry of Commerce & Industry Government of India